The Quality in Electronic Services Jogja City Government: In Case E-KTP - Dody Mulyanto (Laboratorium Jurusan Ilmu Pemerintahan FISIP Universitas Riau, 2019)
This research aims to measure public service satisfaction through the electronic service in jogja city government.Tthis study is a qualitative research with descriptive analytic method. It also analyzest with normative theory as comparison. In this case, the research explore take of e-ktp, E-ktp has a profit for indonesian people who are as identity card, handle the country administration access and facilities easily, minimize dual population data, and there is no need to extend the card (for life). The jogja city government still has a lot of problem. Although 1900 society haven’t receive an E-ktp, then Jogja city government should prepare with 4.0 era in which all of system use elecetronic. The author analyze and think how to increase satisfication quality service through electronic system.